Computer simulation study on the self-assembly of tethered nanoparticles with tunable shapes. Issue 3 (11th January 2019) - Lu, Sheng-Fang; Li, Bing-Yu; Li, Yan-Chun; Lu, Zhong-Yuan
Abstract : The self-assembled structures are characterized by the packing of nanoparticles on the micelle surface, and the typical packing mode turns from rectangular (typical for cubes) to hexagonal (typical for spheres). Abstract : We built a tethered nanoparticle (TNP) model that is composed of a nanoparticle with a hydrophobic tethered polymer chain. The shape of the nanoparticle can be tuned from a pure rigid cube to a soft sphere, mimicking the increase of grafting density on the nanocube surfaces. With this model, we study the self-assembly of TNPs in dilute solution using a dissipative particle dynamics simulation technique, and especially focus on the influence of particle shape, tethered chain length, and grafting density on the self-assembly structures. Some intriguing aggregates such as spherical micelles, pearl-necklace-like structures, cubic columnar structures, handshake structures, core–shell–corona micelles, and four-patch micelles have been observed when varying the interactions between cubes and solvents and the lengths of tethered chain. Modifying the nanocube surface with some hydrophilic grafted chains helps the TNPs form small micelles. Increased steric repulsion due to chain overlapping at larger grafting densities results in shape transformation of the nanoparticle from a rigid cube to a soft sphere. In these cases, the self-assembled structures are characterized by the packing of nanoparticles on the micelle surface, and the typical packing mode turns from rectangular (typical for cubes) to hexagonal (typical for spheres).